CAMPANIILE MEDIATICE – FORME DE PROMOVARE A MESAJELOR SOCIALE - Botnariuc, Marina (CEP USM, 2019)
Mesajele transmise prin intermediul presei au valoare dacă sunt susceptibile să realizeze funcțiile social-comunicaționale și dacă generează reacții din partea publicului. Potențialul campaniilor mediatice de a solidariza publicul poate fi măsurat prin problemele soluționate într-un interval prestabilit de timp.

The messages transmitted through the media have value if they are able to perform the social communication functions and if they generate feedback from the public. The potential media campaigns to show solidarity on behalf of the public can be measured by the problems solved within a predeterminated span of time.
MEDIA CAMPAIGNS AS FORMS OF PROMOTING SOCIAL MESSAGES
Keywords: campanie mediatică; campanie socială; instituție mass - media; mesaj social; valoare socială; media campaign; social campaign; mass - media institution; social message; social value